PENGARUH PROBLEM-BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR MATEMATIKA - Fatimatuz Zahroh (FKIP Unirow Tuban, 2018)
This study aims at determining to examine Problem Based Learning effect on the increase of learning achievement of Mathematics class X-MIA SMA Negeri 1 Lamongan Lesson Year 2017/2018. The research used quantitative approach method (Simple Linear Regression Analysis), collecting data used observation sheet and test analysis instrument, analysis data used SPSS. The results showed 1) Average scores of student learning outcomes with Problem Based Learning amounted to 79.01, but the average score of learning outcomes before with Problem Based Learning is amounted to 71. 2) The test results in the Summary Model table, obtained, Pearson correlation coefficient (R ) equal to 0.694a, R square equal to 0.481 it has influence contribution of 48.1% to variable Y and 51.9% influenced by other factors. 3) Test results in ANOVAb table is F_count of 61.20, sig (0.000a <0.05), then the regression model can be used to predict Learning Outcomes. 4). The result of test on Table Coefficientsa is Constant (a) is 34,388, the effectiveness of learning (b) is 0.705, then the regression equation is Y = 34.388 + 0.705 X, t count of 7.823 with sig (0,000 <0,05) it means between Problem Based Learning (X) on the increase of Learning Outcomes (Y).